2021
DOI: 10.3390/app11125657
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Adaptation Assessment for Two Composite Layering Techniques Using Dye Penetration, AFM, SEM and FTIR: An In-Vitro Comparative Study

Abstract: Do the new, modern dental resin composites improve the sealing in cavities restorations? The present study was designed to compare the effect of two different, but most used layering techniques of the dental composite in reducing the marginal microleakage when a brand-new material is used; Class I black cavities were prepared on 120 human extracted teeth and then restored using oblique and horizontal layering technique. The dye penetration analysis, the atomic force microscopy (AFM), scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Invented in 1931, scanning electron microscopy quickly became a fundamental imaging technique in biomedical studies [ 2 , 25 , 26 ]; an example of its feasibility in dental tissues imaging is presented in Figure 6 and Figure 7 [ 27 , 28 ].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
See 3 more Smart Citations
“…Invented in 1931, scanning electron microscopy quickly became a fundamental imaging technique in biomedical studies [ 2 , 25 , 26 ]; an example of its feasibility in dental tissues imaging is presented in Figure 6 and Figure 7 [ 27 , 28 ].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The obtained spectrum depends on the specimen composition and change in the mineral component is captured [ 22 , 24 ]. The method was used in testing various pre-restoration protocols and its influence on shear bond strength (SBS) [ 28 , 35 , 36 ]. The change in the elemental composition in dentin–resin interface confirmed that the implemented protocols had an impact on SBS [ 27 , 35 , 36 ].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
See 2 more Smart Citations
“…Only caries-free teeth were included in the group, without coronary destruction and without pre-existing restorations. In order to meet the necessary hydration conditions after extraction, these teeth were preserved in distilled water after professional cleaning [6].…”
Section: Preparation Of the Samplesmentioning
confidence: 99%